Histologic diagnosis of metabolic bone diseases: bone histomorphometry - L. Dalle Carbonare; S. Giannini (PAGEPress Publications, 2004)
Histomorphometry or quantitative histology is the analysis on histologic sections of bone resorption parameters, formation and structure. It is the only technique that allows a dynamic evaluation of the activity of bone modelling after labelling with tetracycline. Moreover, the new measurement procedures through the use of the computer allow an assessment of bone microarchitecture too. Histomorphometric bone biopsy is a reliable and well-tolerated procedure. Complications are reported only in 1% of the subjects (hematoma, pain, transient neuralgia). Histomorphometry is used to exclude or confirm the diagnosis of osteomalacia. It is employed in the evaluation of bone damage associated with particular treatments (for example, anticonvulsants) or in case of rare bone diseases (osteogenesis imperfecta, systemic mastocytosis). It is also an essential approach when clinical, biochemical and other diagnostic data are not consistent. Finally, it is a useful method to understand the pathophysiologic mechanisms of drugs. The bone sample is taken at the level of iliac crest under local anesthesia. It is then put into methyl-metacrilate resin where the sections are prepared for the microscopic analysis of the various histomorphometric parameters.